The Role of Epidermal Growth Factor Receptor Family of Receptor Tyrosine Kinases in Mediating Diabetes-Induced Cardiovascular Complications - Bara A. Shraim; Bara A. Shraim; Moaz O. Moursi; Moaz O. Moursi; Ibrahim F. Benter; Abdella M. Habib; Abdella M. Habib; Saghir Akhtar; Saghir Akhtar (Frontiers Media S.A., 2021)
Diabetes mellitus is a major debilitating disease whose global incidence is progressively increasing with currently over 463 million adult sufferers and this figure will likely reach over 700 million by the year 2045. It is the complications of diabetes such as cardiovascular, renal, neuronal and ocular dysfunction that lead to increased patient morbidity and mortality. Of these, cardiovascular complications that can result in stroke and cardiomyopathies are 2- to 5-fold more likely in diabetes but the underlying mechanisms involved in their development are not fully understood. Emerging research suggests that members of the Epidermal Growth Factor Receptor (EGFR/ErbB/HER) family of tyrosine kinases can have a dual role in that they are beneficially required for normal development and physiological functioning of the cardiovascular system (CVS) as well as in salvage pathways following acute cardiac ischemia/reperfusion injury but their chronic dysregulation may also be intricately involved in mediating diabetes-induced cardiovascular pathologies. Here we review the evidence for EGFR/ErbB/HER receptors in mediating these dual roles in the CVS and also discuss their potential interplay with the Renin-Angiotensin-Aldosterone System heptapeptide, Angiotensin-(1-7), as well the arachidonic acid metabolite, 20-HETE (20-hydroxy-5, 8, 11, 14-eicosatetraenoic acid). A greater understanding of the multi-faceted roles of EGFR/ErbB/HER family of tyrosine kinases and their interplay with other key modulators of cardiovascular function could facilitate the development of novel therapeutic strategies for treating diabetes-induced cardiovascular complications.